2013
DOI: 10.1155/2013/171865
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of Pb(II) from Aqueous Solution Using Cow Hooves: Kinetics and Thermodynamics

Abstract: Biosorption of Pb(II) ions from aqueous solution by cow hooves (CHs) was investigated as a function of initial pH, contact time, and biosorbent dosage through batch studies. Equilibrium experiments were performed at three different temperatures (298, 308, and 318 K) using initial Pb 2+ concentration ranging from 15 to 100 mgg −1 . This study revealed that maximum uptake (96.2% removal) of Pb 2+ took place within 30 minutes of agitation, and the process was brought to equilibrium within 60 minutes of equilibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Therefore, an equilibrium time of 90 minutes was used for further experiments. The initial high biosorption rate may be linked to the abundance of free binding sites on the biosorbent which become saturated resulting in decreased biosorption rate [14].…”
Section: Pseudo Second Order Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an equilibrium time of 90 minutes was used for further experiments. The initial high biosorption rate may be linked to the abundance of free binding sites on the biosorbent which become saturated resulting in decreased biosorption rate [14].…”
Section: Pseudo Second Order Kineticsmentioning
confidence: 99%
“…The low price of the Biosorbent is an additional assets, this renders the whole method cheap and allows for combining with other sequestering processes [13]. Recent studies have shown that several Biosorbents like cow hooves [14], egg shell [15], Msasa Tree (brachystegia spiciformis) Leaf Powder [1], chick and Duck Feather [16], pseudomonas aeruginosa DSGPM4 species [17], treculia africana [18], roasted date pits [19], shrimp peel [20], were used for remediation of heavy metals from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metal pollution is a global menace that has threatened the existence of lives for decades. Heavy metals are particularly injurious to plants and animals because of their nonbiodegradability, persistency, and bioaccumulation tendency [1,2]. Nickel can be introduced to the aquatic environment through raw wastewater streams from industrial activities such as mineral processing, paint formulation, electroplating, porcelain enameling, copper sulphate manufacture, manufacture of alloys, silver refining, zinc base casting and storage battery industries, and mining [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Em um processo de adsorção de íons metálicos o ΔG < 0 indica que o processo de adsorção é espontâneo. Essas reações ditas espontâneas ocorrem em um processo exotérmico, na qual há liberação de energia (OSASONA et al, 2013;NUHOGLU E MALKOC, 2009). Por outro lado, em sistemas não espontâneos, ΔG > 0, ocorre a absorção de energia, ou seja, é necessário um fornecimento de energia ao sistema para ocorrer a reação química de maneira a vencer a energia de ativação para a formação de produtos.…”
Section: Modelo De Freundlichunclassified